HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEKERASAN TERHADAP PEREMPUAN PADA REMAJA PUTRI DI SMA KOTA DEPOK TAHUN 2023 - Siska Amanda (2024)
Violence against women in Depok City, which ranked first in West Java with 278 cases, reflects a serious problem that requires in-depth understanding. This cross-sectional study, involving 150 high school students with cluster random sampling, aimed to explore the relationship between knowledge and attitude with violence against women. Bivariate results showed a significant association, with a p-value of 0.022 for the knowledge category and 0.014 for the lack of attitude category. This indicates that the better the knowledge and attitude, the lower the risk of violence against women. Recommendations are given to schools and the Depok City government to integrate violence against women education programs into the school curriculum, with an emphasis on the active role of female students and peer education. The goal is to increase girls' knowledge and positive attitudes towards the issue of violence, contributing to the prevention and protection of women in the school environment.